Direct and indirect effects of carrion subsidies in an arid rangeland: Carrion has positive effects on facultative scavengers and negative effects on a small songbird. (August 2020) - Rees, James D.; Crowther, Mathew S.; Kingsford, Richard T.; Letnic, Mike
Abstract: In the absence of top-down regulation by predators, herbivore populations irrupt. In irrupting populations of large herbivores deaths are frequent and availability of carrion from carcasses is high, potentially subsidising facultative scavengers such as crows and ravens. Increases in facultative scavengers could amplify perceived and real predation risk for small prey. We provisioned large-herbivore carcasses over 2 weeks at three sites (400 ha/site) in the Australian arid zone and monitored detection rates of facultative scavenger birds and low-nesting small passerines at these sites and at three control sites of the same size. We found that provisioning large herbivore carcasses rapidly increased local abundances of scavenging corvids Corvus coronoides and C. bennetti by 50% and decreased relative detection rates of a predation-sensitive small passerine, white-winged fairywren Malurus leucopterus by 50%. White-winged fairywren detection rates were inversely correlated with corvid abundances. Our study indicates that increases in carrion availability associated with herbivore irruptions subsidise facultative scavengers, and thus may indirectly affect co-occurring prey species. Highlights: Humans benefit many facultative scavengers both by directly providing them with food resources and also by manipulating ecosystems in ways that modify resource flows. We experimentally supplemented carrion in an arid environment and monitored the activity of facultative scavengers and small songbirds. Facultative scavengers responded positively and a small passerine, the white winged fairy wren responded negatively to carrion addition. Carrion can have direct and indirect effects on wildlife.